Effect of modulation ratio on microstructure and tribological properties of TiAlN/TiAlCN multilayer coatings prepared by multi-excitation source plasma. (May 2023) - Zhou, Bing; Wang, Yiming; Liu, Zhubo; Zhi, Jiaqi; Sun, Hui; Wang, Yongsheng; Wu, Yanxia; Hei, Hongjun; Yu, Shengwang
Abstract: TiAlN/TiAlCN multilayer coatings with different modulation ratios were prepared by magnetron sputtering and pulse-cathodic arc evaporation. The effect of modulation ratio on the microstructure, composition, surface morphology, mechanical and tribological properties of the coatings was investigated by X-ray diffraction, Raman spectroscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, scanning electron microscopy, nanoindentation and tribological tests. The results showed that the composite structure of nanocrystalline/amorphous phases containing Ti–N/Ti–C, Al–N bonds, and amorphous carbon (sp 3 -C and sp 2 -C) was formed at the interface of the multilayer coatings, and its distribution and composition content could be adjusted by modulation ratio. The TiAlN/TiAlCN multilayer coating with modulation ratio of 1.0 had the highest hardness of 16.7 GPa due to the difference of modulus of each layer, the increase of sp 3 -C bonds and the strengthening of fine grains. The friction experiment revealed that the wear rate of the multilayer coatings reduced significantly with the decrease of modulation ratio. The multilayer coating with modulation ratio of 0.7 had relatively low coefficient of friction and the lowest wear rate. Highlights: TiAlN/TiAlCN multilayer coatings with modulation ratios were prepared using multi-excitation source plasma. Composite structure of nanocrystalline/amorphous phase was formed at the interface region. TiAlN/TiAlCN multilayer coating with modulation ratio of 1.0 had the highest hardness and adhesion strength. Tribological properties of multilayer coatings could be improved by optimizing the modulation ratio.